Understanding structural and functional aspects of PII snake venom metalloproteinases: Characterization of BlatH1, a hemorrhagic dimeric enzyme from the venom of Bothriechis lateralis - Camacho Umaña, Erika (2014)
A new homodimeric PII metalloproteinase, named BlatH1, was purified from the venom of the Central American arboreal viperid snake Bothriechis lateralis by a combination of anion-exchange chromatography, hydrophobic interaction chromatography, and gel filtration. BlatH1 is a glycoprotein of 84 kDa. The mature protein contains a metalloproteinase domain, with the characteristic zinc-binding motif (HEXXHXXGXXH) followed by the sequence CIM at the Met-turn. In the disintegrin domain, the tripeptide sequence TDN substitutes the characteristic RGD motif found in many disintegrins. BlatH1 hydrolyzed azocasein, gelatin and fibrinogen, and exerts a potent local and systemic hemorrhagic activity in mice. The hemorrhagic activity of BlatH1 is not inhibited by the plasma proteinase inhibitor α2-macroglobulin, although the SVMP is able to cleave this plasma inhibitor, generating a 90 kDa product. BlatH1 inhibits ADP- and collagen-induced human platelet aggregation (IC50 = 0.3 μM and 0.7 μM for ADP and collagen, respectively). This activity is abrogated when the enzyme is preincubated with the metalloproteinase inhibitor Batimastat, implying that it depends on proteolysis. In agreement, a synthetic peptide containing the sequence TDN of the disintegrin domain is unable to inhibit platelet aggregation. BlatH1 is a valuable tool to understand the structural determinants of toxicity in PII SVMPs.